Designing a sustainable and resilient agri-food closed-loop supply chain network for porcine products - Álvaro Ronaldo Elizalde Camacho; Fatemeh Gholian-Jouybari; Behzad Mosallanezhad; Neale R. Smith; Mostafa Hajiaghaei-Keshteli (Sustainable Futures)
The sustainability of agri-food supply chains is imperative for addressing global food security while mitigating environmental and socio-economic challenges. This study proposes a multi-product, multi-period closed-loop supply chain network for porcine products, integrating forward and reverse logistics to optimize economic and environmental outcomes. The network encompasses production, processing, distribution, and waste management activities, ensuring alignment with circular economy principles and sustainable development goals. The network is mathematically developed to minimize the net present value of the total cost over the planning horizon. A suite of hybrid metaheuristic algorithms, combining classical and modern approaches, is employed to address the computational complexity. The model is validated through a comprehensive case study conducted in Sonora, Mexico, and tested against fourteen trial scenarios of varying complexity. Results demonstrate the superior performance of the hybrid metaheuristic methods in achieving cost-efficiency. In 86 % of numerical tests, the H_KASA outperforms other proposed algorithms in terms of objective function value. Sensitivity analysis reveals that production capacity and customer demand have a significant impact on supply chain costs, leading to a shift of over 20 % when either parameter increases by 50 %. The findings underscore the potential of integrated closed-loop designs to reduce waste, enhance resource efficiency, and offer practical recommendations for policymakers and key players in the agri-food industry.